Diagnostic performance of magnetic resonance imaging and ultrasonography on the detection of cesarean scar pregnancy: A meta-analysis. Issue 48 (3rd December 2021) - Xiao, Xiaoyi; Ding, Rixing; Peng, Lei; Liu, Huaping; Zhu, Yun
Abstract: Background: : There is still a debate on which imaging method is the best to diagnose cesarean scar pregnancy (CSP). Accordingly, this study aimed to analyze the diagnostic performance of magnetic resonance imaging (MRI) and ultrasonography (US) on the detection of CSP based on current evidence in the literature. Methods: PubMed, Embase, Cochrane, Chinese Biomedical Documentation Service System, WanFang, and China National Knowledge Infrastructure databases were searched up to June 2020. The included studies were all comparisons of MRI and US in the diagnosis of CSP that adopted postoperative histological examination as the reference standard. The pooled sensitivity, specificity, positive likelihood ratio (PLR), negative likelihood ratio (NLR), and area under the summary receiver operating characteristic curve (AUC) were calculated for MRI and US. Results: Thirteen studies were included, with a total sample size of 948 patients. The pooled sensitivity, specificity, PLR, NLR, and AUC of MRI in diagnosing CSP were 0.93 (95% CI, 0.91-0.95), 0.83 (95% CI, 0.75-0.89), 5.46 (95% CI, 3.70-8.05), 0.08 (95% CI, 0.06-0.11), and 0.96 (95% CI, 0.93-0.97), respectively; for US they were 0.84 (95% CI, 0.79-0.88), 0.73 (95% CI, 0.62-0.81), 3.06 (95% CI, 2.22-4.21), 0.23 (95% CI, 0.18-0.28), and 0.86 (95% CI, 0.83-0.89), respectively. Conclusion: We found that both MRI and US effectively diagnosed CSP; however, MRI had a higher diagnostic performance in detecting CSP than US. Abstract : Supplemental Digital Content is available in the text